Knowledge, Attitude and Practices of Pregnant Women Attending University of Ilorin Teaching Hospital with Regard to Rubella - Oluwapelumi Olufemi-Adeyemi; Olajide Olubunmi-Agbede; Olatunji Matthew-Kolawole; Anthony Okoh (Tehran University of Medical Sciences, 2012)
Objective: This study was carried out to clarify the potential health-risk and to determinant the prevalence of antenatal rubella infection in North-Central, Nigeria. Materials and methods: A descriptive cross-sectional survey was carried out among pregnant women to establish the knowledge, attitude and practices with regards to antenatal rubella infection in early pregnancy in Ilorin. A total of 92 subjects were recruited by simple random selection from the antenatal clinics of the University of Ilorin Teaching Hospital, Nigeria. Results: Results showed that congenitally defective eyes or ears were regarded as a greater burden to bear than a congenitally defective heart. Pregnant mothers are more likely to abort a congenitally defective fetus before term. Multigravid pregnant women are more likely to have an abortion (X 2 = 12.48, df = 4, p = 0.014), just as married pregnant women were more likely to abort a congenitally defective fetus before term (X 2 = 23.64, df = 4, p = 0.0). Conclusion: It is a general assumption that Nigeria today is majorly rural, therefore, health educational activities for prompt antenatal reporting in sub-urban Ilorin, and Nigeria as a whole, may be a relevant intervention for pregnant women.